2011
DOI: 10.1177/0021886311407666
|View full text |Cite
|
Sign up to set email alerts
|

Individual Flexibility in the Workplace

Abstract: During the past few decades, scholars have undertaken numerous studies to map various determinants of flexibility at various levels: organizational, group, and individual. However, limited attention has been paid to the role of context and spatiality in realizing individual flexibility. This article aims to fill this gap and seeks to inquire into links between flexibility and spatiality. More specifically, this article will explore how organizational spatial layouts affect individual flexibility as everyday wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 72 publications
6
36
1
Order By: Relevance
“…Although there are studies on diverse physical work environments, such as hospitals (Värlander, 2012), factories (Bernstein, 2012), and hairdressing salons (Shortt, 2015), office environments continue to be of substantial interest for researchers who study physical work environments. Many of the significant 1970's and 1980's studies of physical work environments compared cell and open-plan offices (e.g.…”
Section: A Short History Of Research On Physical Work Environmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Although there are studies on diverse physical work environments, such as hospitals (Värlander, 2012), factories (Bernstein, 2012), and hairdressing salons (Shortt, 2015), office environments continue to be of substantial interest for researchers who study physical work environments. Many of the significant 1970's and 1980's studies of physical work environments compared cell and open-plan offices (e.g.…”
Section: A Short History Of Research On Physical Work Environmentmentioning
confidence: 99%
“…Similarly, Värlander (2012) has demonstrated that in open-plan offices, social rules quickly emerge to limit people's interaction with one another. Employees developed and policed norms related to talking loudly and talking on the phone, which limited the flexibility of the space and employees' behaviour, the outcome the organisation was trying to promote.…”
Section: Current Debates On Open-plan Officesmentioning
confidence: 99%
See 3 more Smart Citations